Flow-synthesis of carboxylate and phosphonate based metal-organic frameworks under non-solvothermal reaction conditions - Waitschat, Steve; Wharmby, Michael T; Stock, Norbert (Dalton transactions : an international journal of inorganic chemistry, 2015)
A continuous flow reactor was developed for the synthesis of porous metal-organic frameworks (MOFs) under mild reaction conditions. Commodity hardware was used to assemble the device, giving it a great degree of flexibility in its configuration. The use of paraffin to encapsulate reactions and also ultrasonic treatment were employed to prevent clogging of the reactor. Reactor design was optimised through studies of the synthesis of zirconium carboxylate framework UiO-66. Synthesis of the aluminium carboxylate CAU-13 was also performed, to demonstrate the versatility of the device. Finally the reactor was used to synthesise a new cadmium phosphonate framework, bearing the STA-12 network.